Computerisation of a corpus of personal correspondence spanning the 19th and 20th centuries: the study of linguistic variation - Perea, Maria-Pilar (Slavia Centralis, 2020)
The article presents the contents and the technical resources of the CD-ROM "Epistolari d’Antoni M. Alcover (1880–1931)" [Antoni M. Alcover’s correspondence], published in 2008, which contains the complete transcription of the Majorcan dialectologist’s personal correspondence between 1880 and 1931. It shows how the computer program can help to study the linguistic variation throughout the 3,529,159 words of the corpus of correspondence. Among many other features, we pay special attention to the presence of dialect features and to the linguistic interference between Catalan and Castilian at the beginning of the 20th century.